2015
DOI: 10.7314/apjcp.2015.16.13.5459
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Childhood Cancer in Northwest Iran

Abstract: This case series study was performed for all 83 children below 14 years old suffering from cancer during 2010-2013 who were registered in Ardabil pediatric cancer registry (APCR). The required data were collected by questionnaire and analyzed with SPSS.19 statistical methods software. Some 51 (61.4%) of cases were male. The mean age of patients was 5.8 years. Of the total, 60 (72.3%) of cases were from urban areas. Results showed that leukemia with 54.2%, CNS with 12% and neuroblastoma with 8.4% were the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
(9 reference statements)
5
11
0
Order By: Relevance
“…These results are similar to other studies. [5,6,7,8,9]. It was found that most common cancer group in the present study were leukemia (54%) followed by lymphoma (8.36%), Brain tumours (7.27%) and Sarcoma (7.27%).…”
Section: Discussionsupporting
confidence: 54%
“…These results are similar to other studies. [5,6,7,8,9]. It was found that most common cancer group in the present study were leukemia (54%) followed by lymphoma (8.36%), Brain tumours (7.27%) and Sarcoma (7.27%).…”
Section: Discussionsupporting
confidence: 54%
“…To make effective health policies, robust documents in population-based cancer registries are required. Although several studies focused on regional cancer registries in Iran (13)(14)(15), there is a remarkable paucity of literature on national and subnational population-based cancer incidence and cancer trend reports in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…It's suggests that twice as many children aged 0-14 years have cancer compared to adolescents aged 15-19 years (Zhu, Pickle, Zou, & Cucinelli, 2014), while data from Egypt has shown that 44% of children aged 0-4 years have cancer, followed by 26% of children aged 9-15 years and 22% of children aged 5-8 years (Malla, 2017). Research in North West Iran indicates that the highest prevalence of cancer occurs in children aged 0-4 years, while in North East Iran, the highest prevalence is in children aged 3-6 years (Fathi, Bahadoram, & Amani, 2015). The research from other Asian countries, Japan, also shows that the highest age group suffering from cancer is the age group of 0-4 years (Katanoda et al, 2017).…”
Section: Age Group Of Pediatric Cancer Patientsmentioning
confidence: 99%